2017
DOI: 10.1111/1541-4337.12263
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Bound to an Insoluble Food Matrix: Their Analysis, Regeneration Behavior, and Physiological Importance

Abstract: Dietary antioxidants play an important role in human health by counteracting oxidative stress and preventing chronic diseases. Most common dietary antioxidants in foods are vitamins, carotenoids, phenolic compounds, sulfurcontaining compounds, and neoformed antioxidants. Antioxidants may be present in free soluble or bound insoluble forms in foods. Antioxidants bound to insoluble food matrices have gained the spotlight because they exert their antioxidant effects much longer than free soluble ones. A direct pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 230 publications
(193 reference statements)
3
34
0
Order By: Relevance
“…However, gallic acid was the only component with higher release after the gastric phase. Such a difference could be related to differential stability and interactions with food matrices of these compounds identified during the digestion period . In oral digestion, the texture of solid food is considerably influenced by mastication, salivation, and amylase, which could result in particle size reduction, carbohydrate cleavage, and phytochemical release .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gallic acid was the only component with higher release after the gastric phase. Such a difference could be related to differential stability and interactions with food matrices of these compounds identified during the digestion period . In oral digestion, the texture of solid food is considerably influenced by mastication, salivation, and amylase, which could result in particle size reduction, carbohydrate cleavage, and phytochemical release .…”
Section: Resultsmentioning
confidence: 99%
“…Such a difference could be related to differential stability and interactions with food matrices of these compounds identified during the digestion period. 34 In oral digestion, the texture of solid food is considerably influenced by mastication, salivation, and amylase, which could result in particle size reduction, carbohydrate cleavage, and phytochemical release. 35 Moreover, the combination of pH change and digestive enzymes in gastrointestinal digestion can also affect the release, partition, and stability of phenolic compounds.…”
Section: Phenolic Profilesmentioning
confidence: 99%
“…Due to the use of numerous plant species as a source of phytotherapeutic products, the study of their antioxidant activity has boomed in recent years [41][42][43]. In plants, the main compounds with antioxidant activity are phenols, as they have an aromatic ring that allows the stabilization and relocation of the unpaired electrons of their structure, thus facilitating the donation of hydrogen atoms and electrons from their hydroxyl groups [44,45]. The total phenol content varies depending on the plant species, plant tissue, developmental stage, and environmental factors, such as temperature, water stress, and light conditions [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Insoluble bound phenolics in maize make up 85% of the total phenolics. Recent studies have revealed that compared to free soluble phenolics, bound phenolics displayed significantly higher antioxidant capacity and had a longer duration of their presence in the plasma [24][25][26][27]. With the help of maize NILs, our study is able to investigate the beneficial property of a specific class of flavonoid compound flavan-4-ol against colonic inflammation within a whole-food matrix.…”
Section: Discussionmentioning
confidence: 99%